Delivering gender justice in academia through gender equality plans? Normative and practical challenges. Issue 3 (30th March 2021) - Clavero, Sara; Galligan, Yvonne
Abstract: This paper employs the concept of epistemic justice to examine the potential for gender equality plans (GEPs) to bring about sustainable transformative change towards gender equality in higher education. Mindful of both the limitations and opportunities of gender policy interventions, the paper highlights the importance of approaching gender inequality as a problem of justice and power rather than as an issue of "loss of talent." The paper draws on Fricker's account of epistemic justice as well as on Bourdieu's analysis of power in the academic field, to evaluate seven GEPs in European universities for their potential to transform gender–power relations in academia. The analysis reveals that insufficient attention is paid to the role of academic power in creating gender injustice at all institutional levels and to the role of organizational culture in the perpetuation of gender inequalities in those settings. The study suggests that the incorporation of an epistemic justice lens in the creation of GEPs would address gendered power relationships and lead to sustainable equitable outcomes.